If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -20x = 42x Combine like terms: 5x + -20x = -15x -15x = 42x Solving -15x = 42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42x' to each side of the equation. -15x + -42x = 42x + -42x Combine like terms: -15x + -42x = -57x -57x = 42x + -42x Combine like terms: 42x + -42x = 0 -57x = 0 Divide each side by '-57'. x = 0 Simplifying x = 0
| (10-b)/b | | 48x^3-18x-3x=0 | | 4x+8=2x+5 | | 0.18/0.54 | | 6x+12=8x-16 | | 0=-16t^2+64t+10 | | 6x+2(-3+2)=-7 | | 0.15(x+20)-0.04(x-60)=1.2 | | 15y+10=13y+4 | | 5(-8x-2)+8x=-1 | | -x+2x+24=18 | | 32=-3x-x | | 6x-7w+5x+8y+4y+5w= | | 0=16t^2+64t+10 | | 0=sec(x)tan(x) | | 32=-3x-y | | 0x+4=-7 | | 6x+-6x+4=-7 | | 6x+-6+4=-7 | | 6x-13-4x=-6x+5(1+2x) | | e+6e= | | -8-2(-2)=-2 | | 12+4h= | | 3x-(0.5x+5)=2 | | x^2+1=5x-5 | | Y=3(4)-14 | | 4(m-2)=m-8 | | (-6x-16)/4 | | -5=-75 | | 23x-84=8 | | 3v^2+21v-40=2v | | Y=8(0)-2 |